Analysis of the absorption spectra of EBT2 and EBT3 radiochromic films - León Marroquín, E Y; Camacho López, A M; García Garduño, A O; Herrera González, A J; Villarreal Barajas, E J; Martínez Quiroz, A C; De la Cruz Pérez, D; Jiménez Avilés, G (Revista Mexicana de Ingenieria Biomedica, 2017)
To analyze the net absorption spectra of EBT2 and EBT3 radiochromic films to describe their influenceon the behavior of dose-response curves. The films were irradiated in a linear accelerator of 6 MV. The net absorption spectra were obtained with a UV / VIS spectrophotometer. Dose-response curves were obtained with a scanner, a He-Ne laser and a spectrophotometer. The absorption spectrum of the EBT2 shows three focused absorption bands that retain position and increase their intensity as a function of dose, however, this behavior is not observed in EBT3 films. The dose-response curve shows maximum sensitivity using the spectrophotometer, but does not show a defined behavior. Generation of new knowledge for the creation of new optical systems capable of amplifying the responsiveness of the films. Show the correlation between net absorption spectra and their influence on dose-response curves in three different optical systems. The behavior of absorption spectra combined with the behavior of the dose-response curves helps to discard the use of optical systems that do not guarantee a reliable clinical use.